Benefits for public healthcare buildings towards Net Zero Energy Buildings (NZEBs): initial reviews - Sulzakimin, M. Sulzakimin; Masrom, M. A. N.; R., Hazli; Ahmodu, Adaji Adejah; Seow, T. W.; A. R., Mohd Hilmi Izwan (2020)
NZEBs concept has received incrementing attention especially since European Union Parliament are progressively moving towards regulation in which all new buildings to be “nearly Zero-Energy” Buildings by 2020. Even though this concept delivers promising benefits, previous studies found that the benefit of NZEB is still in vague to the Malaysian construction industry, mostly for healthcare buildings. The NZEBs concept implementation is critical in healthcare building as it seen as a key part of the needed transition towards sustainable development. This paper aims to define benefits of NZEBs practices through initial investigation among architects. Several existing energies works of literature and pilot studies by using semi-structured interviews were conducted. The findings divulge that, although the term ‘NZEBs design strategies’ is not being used largely across construction industry in Malaysia, some sustainable practices related to the design stage of construction has been implemented. The findings are also promising in growing awareness, practices and implementation of NZEBs design strategies by the practitioner in Malaysia. It is foreseen that the paper will provide a straightforward knowledge for future research in NZEBs design strategies practices for healthcare buildings construction in Malaysia.